Modern technical base of a large library - A. I. Pavlov (Библиосфера)
The history of the development and the results of many years work of the automated library information systems (ALIS) in SPSTL SB RAS, as well as specific technical solutions on various technological levels are described. Operation results of the centralized system of library and information processes automation in the scientific centers of the SB RAS as technologies that are most clearly reflect the prospects of developing ALIS in SPSTL SB RAS are presented.